Gregory the Great’s Greek: Pope Gregory I’s Reception of Nyssen’s Homilies on the Canticle - Porter, Philip G. (Vigiliae Christianae, 2026)
This study investigates Pope Gregory I’s reception of Gregory of Nyssa’s Homilies on the Song of Songs. The claim that Gregory I could read Greek is a minority position in Late Antique Christian studies. This essay reviews the evidence for Gregory I’s knowledge of Greek and answers objections to this position that have been raised in the scholarship. It then proceeds to compare Gregory I’s Commentary on the Song of Songs with Nyssen’s homilies. It provides evidence of direct inheritance, adding to the positive scholarly assessment of Gregory I’s command of Greek. By establishing a direct line of influence from a text that did not exist in Latin translation until the 19th century, this study makes the case for a reevaluation of Gregory I’s language skills and sources and of the state of Roman education in the late sixth and early seventh centuries.